(untitled) (Fiep Bulletin - online, 2015)
The World Congress of Physical and Sportive Education held in Madrid, from 12th to 18 September 1966, will remain in the history of world physical education and of the FIEP as one of the most important events form the cultural point of view, in our epoch.